Development of labor market information system in Indonesia towards world class - Beni Teguh Gunawan; Yeni Nuraeni (Universitas Negeri Yogyakarta, 2023)
The demographic dividen can provide benefits for Indonesia. The proportion of the working age population in Indonesia until 2021 is reaching 205.36 million, which is 68.08% of the workforce. The labor force participation is 93.74%, with the informal sector as much as 59.6%, and the number of unemployed reaches 6.26%. The labourforce structure profile is a challenge for the Indonesian government to encourage the population to participate to industry. The developing of Labour Market Information System (LMIS) is one of the goverment to gather job seekers and employers with the final objective is to reduce unemployment. This study aims to evaluate and analyze the LMIS that has been developed by the Government of Indonesia and to formulate an LMIS development strategy to meets international standards. This study uses qualitative analysis methods. Sampling using purposive sampling technique by taking samples of several provinces that are categorized as densely industrialized and have a high unemployment rate. LMIS owned by Indonesia is still classified as basic level to middle class. Based on the problems that occur in LMIS development and the low level of utilization, the LMIS development method must be based on and pay attention to the needs of stakeholders.